Desain Tongkat Penjepit Multifungsi Menggunakan Metode Fuzzy Analytical Hierarchy Process (FAHP) - Rudiansyah Rudiansyah; Yohanes Yohanes; Anita Susilawati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The multi-function of clamping stick serves to pick up items, to replace light bulbs, to catch snakes, to reach objects in the cupboard that are not reachable to the hands and so on. Its multi-purpose can reduce the process of bending and standing and when pick up objects and collecting waste becomes hygienic. In this research the Fuzzy Analytical Hierarchy Process (FAHP) was chosen as a method to determine the optimal design a multi-function clamping stick which based on the questionnaire given to the expert, to choose the best decision alternative. The initial questionnaire was made to prioritize consumer needs, that used for the initial design. The consumer needs's questionnaire was made on several aspects, namely: flexibility, design, material, safety, usebility, function, dimensions and aesthetics. The next step was the selection of optimal designs using Fuzzy AHP, which involves Experts based on product quality indicators i.e. functional, performance, ergonomic, durability, serviceability and esthetical. The highest indicator value was obtained for Waste Clamping stick of